Global terrorism - Lutz, James M. (Routledge, 2013)
Global Terrorism 3rd edition continues to provide students with the most comprehensive introduction to terrorism as a global phenomenon. It introduces students to history, politics, ideologies and strategies of both contemporary and older terrorist groups. Written in a clear and accessible style, each chapter explains a different aspect of terrorism and illustrates this with a wide variety of detailed case studies from across the world. Although the focus is on the contemporary, the book also includes discussion of older terrorist groups.